The Influence of Organizational Culture and Organizational Citizenship Behavior on Performance Through Job Satisfaction at PT Bank BPD Bali Denpasar Head Office - I Putu WISMAYADI; Endang SUSWATI; M. Jamal Abdul NASIR (International Journal of Environmental, Sustainability, and Social Science, 2023)
Performance is the result of the work of employees or groups of employees during a certain period compared to the performance standards that have been determined by the company. Many variables that influence on it, including organizational culture, organizational citizenship behavior and job satisfaction. This study aims to examine and analyze the effect of: 1) organizational culture on performance, 2) organizational citizenship behavior on performance, 3) organizational culture on job satisfaction, 4) organizational citizenship behavior on job satisfaction, 5) job satisfaction on performance, 6) organizational culture on performance through job satisfaction, 7) organizational citizenship behavior on performance through job satisfaction. This research was conducted at The Bali Regional Development Bank Denpasar Head Office using an explanatory research approach with a census sample technique obtained as many as 57 employees. Data were collected using a questionnaire method given directly to respondents, then analyzed using path analysis. The results conclude that, all the proposed hypotheses are accepted, namely: 1) organizational culture has a significant effect on performance, 2) organizational citizenship behavior has a significant effect on performance, 3) organizational culture has a significant effect on job satisfaction, 4) organizational citizenship behavior has a significant effect on job satisfaction, 5) Job satisfaction has a significant effect on performance, 6) organizational culture has a significant effect on performance through job satisfaction, 7) organizational citizenship behavior has a significant effect on performance through job satisfaction.